Leverage and Dividend Premium as Determinants of Dividend Policy - Fachrezi Mulya Irfan; Lidya Martha (Golden Ratio of Finance Management, 2026)
Dividend policy is an important consideration for investors when making investment decisions. However, previous studies on the effects of leverage and the dividend premium on dividend policy have produced inconsistent findings among companies listed on the Indonesia Stock Exchange. This study aims to analyze the effects of leverage and the dividend premium on dividend policy among companies listed on the Indonesia Stock Exchange during the 2018–2022 period. It is also expected to provide empirical evidence regarding the relevance of Signaling Theory and Catering Theory in explaining dividend policy among publicly listed Indonesian companies. In addition to contributing to the development of the financial management literature, the findings are expected to inform investors and corporate managers seeking to understand the factors that influence dividend distribution decisions amid changing capital market conditions. This study uses a quantitative method and secondary data obtained from corporate financial statements. The sample consists of 32 companies selected through purposive sampling, yielding 160 observations. The data were analyzed using panel data regression with the Common Effect Model (CEM) in EViews 12. The results indicate that leverage has a negative effect on dividend policy, suggesting that higher leverage is associated with a lower tendency to distribute dividends. Meanwhile, the dividend premium has no significant effect on dividend policy. Thus, corporate dividend policy is influenced more strongly by financing structure than by investor preferences reflected in the dividend premium.